Establishment of bladder cancer spheroids and cultured in microfluidic platform for predicting drug response - Qiao Xiong; Ting Liu; Yidie Ying; Xiaowen Yu; Ziwei Wang; Hongliang Gao; Tianhai Lin; Weihua Fan; Zhensheng Zhang; Qiang Wei; Yuqing Ge; Shuxiong Zeng; et al. (Wiley, 2024)
Abstract Cisplatin‐containing combination chemotherapy has been used as the standard treatment for bladder cancer patients at advanced stage. However, nearly 50% of patients are nonresponders. To guide the selection of more effective chemotherapeutic agents, a bladder cancer spheroids microfluidic drug sensitivity analysis system was established in this study. Bladder cancer spheroids were established and successfully cultured in a customized microfluidic device to assess their response to different chemotherapeutic agents. The in vitro drug sensitivity results were also compared to patient‐derived xenograft (PDX) models and clinical responses of patients. As a result, bladder cancer spheroids faithfully recapitulate the histopathological and genetic features of their corresponding parental tumors. Furthermore, the in vitro drug sensitivity outcomes of spheroids (n = 8) demonstrated a high level of correlation with the PDX (n = 2) and clinical response in patients (n = 2). Our study highlights the potential of combining bladder cancer spheroids and microfluidic devices as an efficient and accurate platform for personalized selection of chemotherapeutic agents.